2015
DOI: 10.1080/15592294.2015.1091145
|View full text |Cite
|
Sign up to set email alerts
|

Minimal role of base excision repair in TET-induced global DNA demethylation in HEK293T cells

Abstract: Oxidation of 5-methylcytosine by TET family proteins can induce DNA replication-dependent (passive) DNA demethylation and base excision repair (BER)-based (active) DNA demethylation. The balance of active vs. passive TET-induced demethylation remains incompletely determined. In the context of large scale DNA demethylation, active demethylation may require massive induction of the DNA repair machinery and thus compromise genome stability. To study this issue, we constructed a tetracycline-controlled TET-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…Therefore, these data suggest that TET2-mediated active demethylation may be a threat to genome stability and should not be used to entirely demethylate the genome, but only specific loci. In accordance with our results, Jin et al have recently shown that the BER pathway plays only a minor role in the TET1-mediated global DNA demethylation [35].…”
Section: Impact Of Tet2-induced 5-hmc On Mutagenesissupporting
confidence: 94%
See 1 more Smart Citation
“…Therefore, these data suggest that TET2-mediated active demethylation may be a threat to genome stability and should not be used to entirely demethylate the genome, but only specific loci. In accordance with our results, Jin et al have recently shown that the BER pathway plays only a minor role in the TET1-mediated global DNA demethylation [35].…”
Section: Impact Of Tet2-induced 5-hmc On Mutagenesissupporting
confidence: 94%
“…This cell cycle delay could be linked to the generation of 5-hmC, 5-fC or 5-caC residues which might either (i) perturb DNA replication by themselves or by generating genotoxic DNA repair intermediates such as AP sites and DNA strand breaks by TDG-BER [8,10,13] or (ii) activate intra-S checkpoints as suggested by P53 activation, possibly through ATM/ATR and CHK1/CHK2 pathways. Increase in ␥-H2AX foci formation and activation of CHK2 and P53 have also been observed with TET1 catalytic domain, suggesting a TET1-mediated role in increased DNA damages or decreased DNA repair [35]. Moreover, TET2-mediated 5-hmC has recently been found to colocalize with ␥-H2AX and to participate to DNA damage foci [36].…”
Section: Impact Of Tet2-induced 5-hmc On Cell Cyclementioning
confidence: 91%
“…Genome-wide studies using ChIP-based technologies have shown that the majority of ERα binding sites in breast cancer cells are found distally from gene promoters, and a significant component is found within gene-specific “enhancer” regions in response to the E2 [ 2 ]. Enhancers are essential regulatory regions found in noncoding regions that control temporal and tissue-specific gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the base (or a nearby base) is always first modified, either by deamination, oxidation, or -according to models that now appear less likely -a combination of both, followed by replacement of the modified nucleotide (possibly together with surrounding nucleotides [18,19]). Most evidence points to the base excision repair (BER) pathway [20][21][22][23][24], but its role in global DNA demethylation has been challenged [25]. Alternative pathways include nucleotide excision [26,27] and non-canonical mismatch repair [28].…”
Section: Introductionmentioning
confidence: 99%